When Character Was King - A story of Ronald Reagan - Peggy Noonan (Hawthorn Penguin Books Australia, 2002)
No one has ever captured Ronald Reagan like Peggy Noonan. In When Character Was King, Noonan brings her own reflections on Reagan to bear as well as new stories--from Presidents George W. Bush and his father, George H. W. Bush, his Secret Service men and White House colleagues, his wife, his daughter Patti Davis, and his close friends--to reveal the true nature of a man even his opponents now view as a maker of big history. Marked by incisive wit and elegant prose, When Character Was King will both enlighten and move readers. It may well be the last word on Ronald Reagan, not only as a leader but as a man.
Keywords: Biography -- Biography; US history -- US history